Factores predisponentes para embarazo adolescente en el colegio particular Eugenio Espejo y la unidad educativa San Francisco de Asís de la ciudad de Loja, Agosto 2016 Julio 2017 - Ojeda Vivanco, Pablo Daniel (2018)
Abstract:The purpose of de current investigation is to identify the risk factors that lead to teenager pregnancy at Eugenio Espejo and San Francisco high schools. The process of the investigation began with a sample group of 140 teenagers from both high schools. In order to proceed with the research, every teenager was asked to bring a written consent form signed by their guardian, giving us authorization to proceed with the investigation. Once consent was given, I was able to start with the surveys and the application of the test to determine levels of depression, anxiety, sefl-esteem and the functionality of their families. This project intents to establish itself as descriptive transversal research. Twenty-five risk factors were identify for the teenagers of this high schools. The main risk factor is one related to myths believed by teenagers about their sexual activity. Another important risk factor is the influence each teenage experiences from their peers and the media when considering sexual intercourse. Teenager anxiety occupies the third place as a risk factor.